Cyber Public Relations “Ketimbang Ngemis Jakarta” Melalui Instagram - Ramadhanty, Sucianty; Zebua, Winda Dwi Astuti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Cyber public relations has now become a trend that certainly encourages public relations practitioners to be more practical, fast, and also dynamic in doing their work.  Social media becomes one of the media that is very active and effective in conveying information on the implementation of cyber public relations. This research aims to describe cyber public relations conducted by the nonprofit organization “Ketimbang Ngemis Jakarta” through instagram social media as a form of public relations activities. This research is conducted with a qualitative research approach. The study did not test a hypothesis, but rather emphasized data collection to describe the actual state of the field. The data collection technique is conducted using interviews with two key informants and two informants triangulation of sources, observations, and documentation. The data analysis techniques for the study used interactive data analysis models by Matthew B. Miles and A. Michael Huberman. These include data reduction, data presentation, inference or validation. The results show how “Ketimbang Ngemis Jakarta” runs cyber public relations in accordance with the concept of cyber public relations from Dasrun Hidayat, namely with direct feedback characteristics, competitive opportunities, two-way communication, strengthening communication relationships, and saving.